A bibliometric analysis of opioid in Malaysia - Zin, Che Suraya; Abdullah, Nor Asma Diyana; Ramli, Noorul Atiqah; Khadir, Noorsyahiruh; Zain, Nor Shahfiza; Rosley, Nor Fatin; Shaikh Rahman Bux, Siti Halimah Bux (Wolters Kluwer Medknow Publications, 2020)
Opioid analgesics have been widely used for the treatment of pain. In USA, it was reported an increase in opioid prescribing is parallel with the increase of opioid use disorders such as misuse, abuse, and opioids overdose-related death. Little is known about the opioid situation and its related research in Malaysia.Therefore, this bibliometric study provided an overview on the productivity of opioid research in Malaysia. All published articles on opioid research in Malaysia from 2006 to 2018 were included, where they were retrieved from online databases. Then, the data were analysed, presented and discussed using standard bibliometric indicators, such as growth of publications, number of citation journals, geographical distribution, and issues addressed in the publications. Total of 78 research articles on opioids published between 2006 and 2018 were identified. The relative growth rate (RGR) of publications during the study period was 12.24%. The most common issue studied was the methadone maintenance therapy. Most articles were published in the indexed journals (98.72%) and the predominant journal was the Drug and Alcohol Dependence (11.54%). The article on buprenorphine and naltrexone reported the highest citations of 85. It can be concluded that research evaluating opioids in pain management particularly in patients with non-cancer pain in Malaysia is limited and requires further exploration.